PERBEDAAN SIFAT-SIFAT TANAH VERTISOL DARI BERBAGAI BAHAN INDUK - B. H. Prasetyo (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
Vertisols is black and fertile soils, derived from various parent materials, dominated by smectite clay minerals, and charasterize by crack formation during dry season. Six soil profiles consisted of thirty two soil samples from dIfferent location were analyzed for their chemical and mineralogical composition at the laboratories of Soil Research Center for soil characteristics. Results indicate that the color matrix of Vertisols varies, hue range from 2.5Y to 10YR, color value varies from 2 to 6, and chroma range from 0 to 4. Clay mineral composition of Vertisols is dominated by smectite. Other clay minerals founded in the Vertisols are kaolinite, illite and vermiculite. The mineralogy composition of sand fraction is varies, some of them rich in weatherable minerals like andesine, amfibole, orthoclase, sanidin and the others are dominated by resistant minerals such as quartz and opaque. The mineralogical composition of Vertisols dependent on their parent material. The dominant cations in Vertisols are Ca++ and Mg++. Vertisols from volcanic materials is dominated by Ca++ and followed by Mg++ cations, Vertisols from limestone is dominated by Ca++, while Vertisols from peridotite is dominated by Mg++. All of the Vertisols studied have a high cation exchange capacity with pH’s range from 5.5 to 7.4. In using Vertisols for food plantation, should be consider the high content of Ca++, Mg++ and the water management. The soils should be atleast always in moist condition, otherwise soils become very hard and cracks when dry.